Akar Bahar Craft a Business Development Strategy to Increase Income - Fetri Setyo Liyundira; Khoirul Ifa; Kasno Kasno (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2022)
In the era of the modern economy, producers not only sell their products directly to final consumers, but also use the services of various parties such as intermediary agents and distributors. People's income can certainly be obtained with the success of how to manage finances, product innovation and marketing. This study uses primary data by distributing questionnaires to Akar Bahar craftsmen. There are three factors examined in this study, firstly financial management, knowledge of financial management in the business is still relatively low so they think they don't really need financial management in stabilizing and increasing people's income because the income they earn will be replayed as business capital. Furthermore product innovation which is also not related to the income because product innovation may only be for sweeteners will not change or increase people's income, especially Akar Bahar craftsmen because it is considered too much time wasted to expand the line, adding new products because of the old product it can still be sold. The third, marketing is very closely related to people's income, because marketing is an important activity of all business carried out by companies, especially for profit-oriented companies in an effort to meet consumer needs and desires.